Video Game Writing: From Macro to Micro - Suckling, Maurice; Walton, Marek (Mercury Learning & Information, 2017)
This insightful, revised book explores the challenging and evolving world of the games writer. Part I provides a fascinating overview of the history of games writing following its humble roots in the '60s to today's triple-A titles; Part II asks and answers the key question: what does a games writer do and how do they do it? Especially useful reading for novice game writers, its chapters cover a broad range of topics including contracts, NDAs, creative collaboration, narrative design, editing, adaptations, and environmental storytelling. Part III, of particular value for more advanced students of writing, addresses deeper theoretical questions increasingly relevant in today's games titles, including: Why have story at all? What is plot and how does it work? How best can a writer use agency? Finally, Part IV presents readers with hard-earned nuggets of wisdom from today's game writers working in the US, Europe, and Japan. Packed with practical samples, case studies, and exercises, this book is essential reading for anyone interested in the world of games writing.Features:* Covers history of games writing, narrative design, storytelling, plot, contracts, and packed with practical samples, case studies, and exercises* Presents readers with opinions and suggestions from today's game writers who are working in the US, Europe, and Japan* Includes a broad range of topics e.g., creative collaboration, editing, adaptations, and environmental storytelling* Mentions games such as Elder Scrolls V: Skyrim, Borderlands 2, The Walking Dead, L.A. Noire, Grand Theft Auto V, Mass Effect 3, The Stanley Parable, The Last of Us, Alien Isolation, The Witcher 3: Wild Hunt, Life is Strange, Until Dawn, Quantum Break, BioShock, World of Warcraft, and more.